Solea senegalensis sperm cryopreservation: new insights on sperm quality - F RIESCO, MARTA (2017)
Cryopreservation of Senegalese sole sperm can represent an alternative to overcome some reproductive problems of this species. However, it is important to guarantee the safe use of cryopreserved sperm by selecting an appropriate protocol according to a high demand quality need to be ensured. It has been demonstrated that traditional assays such as motility and viability do not provide enough information to identify specific damage caused by cryopreservation process (freezing and thawing). Specific tests, including lipid peroxidation and DNA damage, should be performed. In the present study, motility and lipid peroxidation were performed as specific tests allowing us to discard cryopreservation conditions such as methanol as internal cryoprotectant and bovine serum albumin as external cryoprotectant. In addition, a caspase 3/7 detection by flow cytometry was performed to analyze apoptosis activity in the best selected conditions. Moreover, new highly sensitive tests based on transcript number detection have recently been described in fish sperm cryopreservation. For this reason, a transcript level detection assay was performed on certain oxidative and chaperone genes related to fertilization ability and embryo development (hsp70, hsp90BB, hsp90AA, gpx) to select the best cryopreservation conditions. DMSO+ egg yolk proved to be the best cryoprotectant combination in terms of transcript level. This study describes an optimized cryopreservation protocol for Solea senegalensis sperm demonstrating for the first time that transcript degradation is the most sensitive predictor of cell status in this species after cryopreservation.